Bioinspired Hydroxyapatite/Poly(methyl methacrylate) Composite with a Nacre‐Mimetic Architecture by a Bidirectional Freezing Method. Issue 1 (10th November 2015) - Bai, Hao; Walsh, Flynn; Gludovatz, Bernd; Delattre, Benjamin; Huang, Caili; Chen, Yuan; Tomsia, Antoni P.; Ritchie, Robert O.
Abstract : Using a bidirectional freezing technique, combined with uniaxial pressing and in situ polymerization, "nacre‐mimetic" hydroxyapatite/poly(methyl methacrylate) (PMMA) composites are developed by processing large‐scale aligned lamellar ceramic scaffolds. Structural and mechanical characterization shows "brick‐and‐mortar" structures, akin to nacre, with interesting combinations of strength, stiffness, and work of fracture, which provide a pathway to making strong and tough lightweight materials.